QUESTIONING THE INFLUENCE OF RELIGIOSITY, SOCIAL CONCERN, AND COMMUNITY INCOME ON THE INTENTION OF PAYING ZAKAT AT BAZNAS - Prawiro, Atmo; Aryani, Fitri; Fata, Ahmad Khoirul (State Islamic University North Sumatra, 2023)
Abstract: The purpose of this study is to prove whether there is an influence of religiosity, social care, and income on interest in tithing through BAZNAS and to prove the knowledge’s role of zakat as an intervening variable. This research was conducted on Bogor City residents who pay Zakat Maal and Zakat Fitrah at BAZNAS Bogor City. This research used a mixed method and used questionnaires and interviews as the data collection. By using SEM-PLS as data processing, the results showed that religiosity and income variables had no effect while social care and knowledge of zakat had an influence on interest in zakat through BAZNAS, and knowledge of zakat could mediate the effect of social concern and income but it could not mediate the effect of religiosity interest in zakat through BAZNAS. The quantitative data is supported by the results of interviews with two informants.Keywords: religiosity, social care, income, zakat knowledge, SEM-PLS.